Transaxillary Subpectoral Placement of Cardiac Implantable Electronic Devices in Young Female Patients - Oh, Joo Hyun; Kim, Chae Min; Song, Seung Yong; Uhm, Jae Sun; Lew, Dae Hyun; Lee, Dong Won (Archives of Plastic Surgery, 2017)
Background The current indications of cardiac implantable electronic devices (CIEDs) have expanded to include young patients with serious cardiac risk factors, but CIED placement has the disadvantage of involving unsightly scarring and bulging of the chest wall. A collaborative team of cardiologists and plastic surgeons developed a technique for the subpectoral placement of CIEDs in young female patients via a transaxillary approach.Methods From July 2012 to December 2015, subpectoral CIED placement via an axillary incision was performed in 10 young female patients, with a mean age of 25.9 years and mean body mass index of 20.1 kg/m2. In the supine position, with the patient's shoulder abducted, an approximately 5-cm linear incision was made along one of the deepest axillary creases. The submuscular plane was identified at the lateral border of the pectoralis major, and the dissection continued over the clavipectoral fascia until the subpectoral pocket could securely receive a pulse generator. Slight upward dissection also exposed an entrance to the subclavian vein, allowing the cardiology team to gain access to the vein. One patient with dilated cardiomyopathy underwent augmentation mammoplasty and CIED insertion simultaneously.Results One case of late-onset device infection occurred. All patients were highly satisfied with the results and reported that they would recommend the procedure to others.Conclusions With superior aesthetic outcomes compared to conventional methods, the subpectoral placement of CIEDs via a transaxillary approach is an effective, single-incision method to hide operative scarring and minimize bulging of the device, and is particularly beneficial for young female or lean patients.
Keywords: Defibrillators, implantable; Pacemaker, artificial; Cardiac resynchronization therapy